1987
DOI: 10.1037/0022-3514.52.3.586
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hypnotic susceptibility: Interpersonal and rapport factors.

Abstract: This research supported the hypothesis that hypnosis can be thought of as a set of potentially modifiable social-cognitive skills and attitudes. A low-interpersonal-training treatment devised by Gorassini and Spanos (1986) was compared with a treatment designed to modify not only cognitive factors but also to augment rapport with the trainer and diminish resistance to responding (high-interpersonal training). Fifty percent of the initially unhypnotizable subjects in the high-interpersonal condition tested as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 43 publications
6
48
0
2
Order By: Relevance
“…In addition, the findings with the subjective scales were similar. These results are consistent with those obtained in the Carleton laboratory (Bertrand, 1989;Spanos, 1986), as well as with those obtained in previous studies that employed the CSTP outside of Carleton (Gfeller et al, 1987;Kirkeby, 1989).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, the findings with the subjective scales were similar. These results are consistent with those obtained in the Carleton laboratory (Bertrand, 1989;Spanos, 1986), as well as with those obtained in previous studies that employed the CSTP outside of Carleton (Gfeller et al, 1987;Kirkeby, 1989).…”
Section: Discussionsupporting
confidence: 94%
“…At least two recent studies (Gfeller et al, 1987;Kirkeby 1989) that were conducted at laboratories other than Carleton found that CSTP-trained subjects exhibited substantially larger gains on behavioral and subjective indexes of susceptibility than did no-treatment control subjects. In addition, Gfeller et al (1987) included a follow-up session which indicated that skill-trained subjects attained substantially higher posttest scores than controls on a standard susceptibility scale as well as on a series of novel and difficult suggestions.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…An intervention that increased participant rapport with the experimenter engendered enhanced hypnotic responsiveness (Gfeller, Lynn, & Pribble, 1987). However, highly suggestible participants persist in being responsive to suggestions, even in the face of interpersonal exchanges prior to hypnosis that effect low rapport (Lynn et al, 1991), implying that low rapport does not vitiate a robust cognitive commitment to respond in these individuals.…”
Section: Social Cognitionmentioning
confidence: 99%